Hubungan Diet dan Olahraga dengan Kestabilan Gula Darah Pada Penderita Diabetes Melitus yang Berobat di Poliklinik Penyakit Dalam RSUD Dr. M. Yunus Bengkulu - Ida Rahmawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2019)
Non-compliance with diet and exercise will result in complications in patients with diabetes melitus, therefore patients must learn special skills to care for themselves every day, in order to avoid a decrease or increase in sudden blood glucose levels, while also having preventive behaviors in lifestyle to avoid longterm diabetic complications. The aims of this study was to determine the relationship between diet and Excercise with Stability of glucose on patients with Diabetes Melitus who treated at Polyclinic RSUD Dr. M. Yunus Bengkulu. This study used cross sectional. Population in this study were all patients with diabetes melitus who treated at Polyclinic RSUD Dr. M. Yunus Bengkul. Collecting data used primary and secondary data. Data analysis used Chi-Square test ( closesness of relationship used Contingency Coefficient (C). The results of this study showed: (1) from 49 respondents, there were 26 people (53%) obedient with diet and 23 people (46,9%) did not obedient with diet. (2) from 49 people there were 38 (77,6%) obedient with excercise and 11 people (22,4%) did not obedient with excercise. (3) There was significant relationship between diet with stability of glucose on patients with Diabetes Melitus who treated at Polyclinic RSUD Dr. M. Yunus Bengkulu. (4) There was significant relationship between excercise with stability of glucose on patients with Diabetes Melitus who treated at Polyclinic RSUD Dr. M. Yunus Bengkulu. Compliance with diet and exercise will be able to control sugar levels in the blood of diabetics